Stock returns-inflation nexus in Indonesia: Evidence from conventional and Islamic stocks - Yahya; Muhammad Shabri Abdul Majid; Hafasnuddin (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to empirically explore the effects of actual, expected, and unexpected inflation on conventional and Islamic stock markets in Indonesia. Research Design & Methods: In the first stage, an auto-regressive integrated moving average (ARIMA) model is utilized to measure expected and unexpected inflations. In the second stage, a dynamic ordinary least squares (DOLS) estimator is used to explore the stock return-inflation nexus over the period from 1999 to 2019. Findings: The study documented that Islamic stock returns are independent of inflation following the Fisher hypothesis. Meanwhile, a negative relationship between stock returns and inflation is found in the conventional stock market. However, the Fama proxy hypothesis was incapable of describing the negative conventional stock returns-inflation relation in its entirety. However, our findings support the Mundell-Tobin hypothesis. Implications & Recommendations: Our findings imply that the Islamic stock market of Indonesia provides a full hedge against actual, while the conventional stock market does not. Contribution & Value Added: This study is the first attempt in the Islamic finance literature to comparatively explore the effects of inflation, expected, and unexpected inflation on conventional and Islamic stock markets from the perspective of the emerging Indonesian economy.
Keywords: C22; C58; G11; 330; Fisher hypothesis; Fama proxy hypothesis; Islamic stock; hedge